35.1: Distinguished Paper: Auto‐Calibration for Screen Correction and Point Cloud Generation. Issue 1 (June 2015) - Deglint, Jason; Cameron, Andrew; Scharfenberger, Christian; Lamm, Mark; Wong, Alexander; Clausi, David
Abstract : Showing a checkerboard at different poses for camera projector calibration is impractical for large scale applications such as projection mapping onto buildings. We use an automatic calibration technique that projects Gray code structured light patterns, which, extracted by the camera, build a dense correspondence for calibration. Two applications benefit from automatic calibration: 3D model generation and screen correction.